Ultrasonographic and pedobarographic evaluation of the effectiveness of extracorporeal shock wave therapy in patients with plantar fasciitis - Alkan, Gokhan; Elbasti, Muhammet Sahin; Akgol, Gurkan; Gulkesen, Arif; Ulusoy, Hasan (Sage Publications Inc, 2025)
Background Prior studies showing the effectiveness of extracorporeal shock wave therapy (ESWT) in patients with plantar fasciitis are mostly based on patient-reported measurements.Objective The aim of this study was to demonstrate the effectiveness of ESWT with ultrasonographic and pedobarographic measurements.Methods A total of 50 patients were included in the study. All patients were evaluated before and six weeks after ESWT treatment. Pain was evaluated with the Visual Analogue Scale (VAS), functional status with Foot Function Index (FFI), and quality of life with Short Form-36 (SF-36). Plantar pressure measurements were made with a pedobarography device, and plantar fascia thickness was measured with ultrasonography.Results After treatment, VAS-Pain decreased significantly. There was a statistically significant improvement in FFI scores after treatment. Similarly, a statistically significant improvement was seen in SF-36 scores. There was a significant decrease in ultrasonographic measurements of the plantar fascia thickness in the origo and midsection regions. There was a statistically significant decrease only in medial heel pressure measurements.Conclusion The results of this study showed that ESWT provides symptomatic and functional improvements in patients with plantar fasciitis as well as ultrasonographic plantar fascia thickness and pedobarographic medial heel pressure measurements.
Keywords: plantar fasciitis; plantar fascia thickness; pedobarographic measurements; ESWT